PENANGKAP IKAN BERBASIS CODE OF CONDUCT FOR RESPONSIBLE FISHERIES (CCRF) DI TEMPAT PELELANGAN IKAN (TPI) INEGO, GORONTALO - Syamsuddin, Syamsuddin (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
Fish resource management is closely related to the management of fishing operations and the fishing targets carried out. The development of fishing activities in the world continues to increase and has shown symptoms of overfishing, one of which is in TPI Inego waters. The fishing gear available at the Inego Fish Auction Place (TPI) is gillnet, trap and mini purse seine fishing gear. The aim of this research is to analyze fishing units that comply with the Code of Conduct Responsible for Fisheries (CCRF) at TPI Inego, Bonebolango Regency. The research method used was a descriptive survey method with a quota purposive random sampling technique, from April to June 2021. The results obtained from this research were that the Gill net and Trap (trap) fishing gear were environmentally friendly fishing gear with each score being valuable. 33.20 and 35.70; and the mini purse saine fishing gear with a score of 17.5 is a fishing gear that is not environmentally friendly.